Unusual thrombosis or pregnancy complications associated to ovarian cancers: two clinical cases. (3rd May 2021) - Vorobev, Alexander; Makatsariya, Alexander; Bitsadze, Viktoriya; Khizroeva, Jamilya; Solopova, Antonina
Abstract: Aim: Using illustrative cases of two patients with ovarian cancer who developed unusual thrombosis in pregnancy, to describe the difficulties in diagnosing and managing such patients. Methods: We present the analysis of two cases of thrombosis of unusual localization (central artery of the retina and transverse and sigmoid sinus thrombosis) during pregnancy in women with hidden ovarian cancer. Results: In both cases, the symptomatic of unususal thrombosis was interpreted as a manifestation of eclampsia, leading to a choice of non-optimal obstetric tactics on a background of hidden ovarian cancer, which in both cases were diagnosed only postpartum Conclusions: Pregnancy itself is a risk factor for thrombotic complications and in case malignancy develops in parallel with pregnancy, this risk is multiplied. In patients with ovarian cancer, difficulties arise both in detecting the tumor itself due to the enlarged uterus and in interpreting some of the symptoms, which can be regarded as a manifestation of pregnancy complications.